ROLAND BARTHES’S THEORY OF SEMIOTICS ANALYSIS IN THE KOREAN DRAMA LOVELY RUNNER - Resfika, Diah Amanda; Sulistyo, Teguh; Cholifah, Maria (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2025)
This study examines the application of Roland Barthes's semiotic theory in analyzing the Korean drama "Lovely Runner," focusing on the emotional dynamics and character development of Ryu Sunjae and Im Sol. The research aims to uncover how various visual signs, including the total solar eclipse scene, yeonji gonji (rouge on the cheeks) scene, the umbrellas, Sunjae’s wristwatch, the sunflowers, and samgyetang, convey the characters' feelings and emotional journeys. Utilizing a descriptive qualitative method, the analysis highlights the denotative and connotative meanings of these symbols, revealing their significance in the narrative. The findings indicate that one visual sign can articulate the emotions of both characters simultaneously, while also expressing the emotional states of a character across different scenes and settings. This study contributes to the literature on semiotics, particularly within the context of Korean dramas, and emphasizes the importance of visual symbols in conveying emotional depth and character development. Ultimately, the research underscores the potential of visual storytelling as a powerful medium for exploring the character's feelings and emotions.